Control of Anthracnose Caused by Colletotrichum Gloeosporioides in Calcium Nitrate Foliar-Sprayed Dioscorea Alata Variety Agbodo - Otusanya, M. O.; Afolabi, C. G. (European Journal of Applied Sciences, 2022)
This study investigated the effect of calcium nitrate foliar spray on Anthracnose disease caused by Colletotrichum gloeosporioides Penz in the Nigerian water yam Dioscorea alata variety Agbodo. The field experiment was a randomized complete block design (RCBD) with three replications. Calcium nitrate at the rates 0mgl-1 (control), 5mgl-1 and 10mgl-1 were sprayed on the plants at 12 weeks after planting (12 WAP). No surfactant was added to the nutrient spray. Disease incidence in the contral was 54.44% and 65.00% at 20 WAP and 24 WAP significantly higher than the two calcium nitrate treatments which had overall mean of 47.23% and 48.06% at 20 WAP and 24 WAP respectively. Anthracnose disease severity score (DSS) which was similar across treatments at 20 WAP was at resistant level, overall mean score of 1.38. DSS was also similar across treatments at 24WAP but had moved up to moderately resistant category with overall mean of 1.69. Previous reports of calcium nitrate foliar spray for anthracnose control in Dioscerea species were with concentrations of 100mgl-1 up to 12000mgl-1 and with addition of Polysorbate 20 as surfactant in the liquid. Further trials with calcium nitrate concentrations similar or lower than that used in this study without surfactant and sprayed twice at 12WAP and 20WAP, and severity assessed at 20WAP, 24WAP and 32WAP is suggested for reduction of severity to resistant level in water yam variety Agbodo and other Nigerian water yam varieties. Total phenolic compounds (TPC) content of variety Agbodo leaves at 24WAP was 3.85mg GAE/g dm in the 10mgl-1 treatment, significantly higher than the 5mgl-1 treatment content of 3.33mg GAE/g dm, which was in turn higher than control TPC content of 2.93mg GAE/g dm. Phenolic compounds in leaves of water yam have been reported to be responsible for resistance to anthracnose, therefore calcium nitrate foliar spray concentrations similar or lower than that in this study are recommended for trials to reduce severity to resistant level in water yam Agbodo and other water yam varieties. Leaf calcium, nitrogen, phosphorus, potassium and sulphur all increased from the 5mgl-1 treatment to the 10mgl-1 treatment (as with TPC), and also were significantly higher than the control. The overall means were 9.35mg/100g dm for Ca, 0.775% for N, 34.37mg/100g dm for P, 196.05mg/100g dm for K and 1.59% for S. Leaf magnesium (Mg) was similar across treatments with overall mean of 17.13mg/100g dm. Increased calcium will favour resistance to anthracnose because of calcium role in membrane function and stability and cell wall integrity. Increased leaf N in relation to disease resistance is reported to be pathogen-specific and will increase resistance especially for facultative parasites such as Colletotrichum gloeosporioides. This is because increase in nitrogen supports metabolic activities of host cells which favour obligate parasites but will not favour facultative parasites as the latter are semi-saprophytes which prefer senescing plant tissue or alternatively produce, toxins to kill host plant cells.